SUSTAINABLE GROWTH RATE OF AGRICULTURAL AND FOOD ENTERPRISES IN SERBIA - Jović, Zoran; Vićentijević, Kosana; Glišović, Nataša (Economics of Agriculture, 2016)
Many proftable businesses can get bankrupt if they grow too slowly or too fast. In order to assess whether a company is growing too slowly or too fast, it is necessary to establish a sustainable growth rate, that represents the maximum growth rate which the company can achieve without additional debt growing. The aim of this study is to determine the sustainable growth rate for the enterprises of the agricultural and food sector in Serbia in 2012 and 2013 and to determine whether there are differences between these two interconnected sectors. The construction sector which is not reproductively connected with agriculture and food ones, was introduced in the study as a control sector. The aim is also to establish a real sustainable growth rate of observed sectors in Serbia taking into consideration the inflation rate which in Serbia has visible fluctuations for the observed years. Real sustainable growth rate serves as a landmark for drawing conclusions about the development potential of these branches and as a conclusion of which internal or external incentives are needed to further increase sustainable growth rate, namely potential for growth. Limitation of the work scope focused research on identifying sustainable growth rate and mutual comparison of observed sectors and provided a basis for further research in the direction of the comparative analysis within the agricultural sector, as well as for determining agricultural activities with the greatest growth potential, expressed through the sustainable growth rate.